Österreichische Architekten in Bulgarien 1878-1918 - Doytchinov, Grigor (2001)
The authors have taken as target of the research project to draw up a picture of the architectural influences and the heritage of the Danubian Monarchy in Bulgaria at the turn of the century. On this way one unknown site of the architecture of the Danubian Monarchy is being cleared up. The contribution of the specialists from the Danubian Monarchy and of the Bulgarian architects educated there is being presented in the first part of the research project. The study starts out from the complex and multifarious cultural context of the European turn of the century and the political changes in southeastern Europe at this time. The decisive contribution of the specialists from the Monarchy in the field of urban design is being duplicated. The architectural influences of the Monarchy are studied in the finale chapter. The phenomenon of the willing acceptance of strange cultural elements is being explained. A chapter is devoted to the specific phenomenon of the Bulgarian National Romantic because there are detected important contributions of graduates from the architectural schools of the Monarchy. In the second part of the research project the fundamental information to the different architects and artists is being summarised in a catalogue. There are biographic descriptions of 66 persons, a listing of works and their illustrations, as well as the resources of information to be found. The work is illustrated with a maximum number of authentic documents. The shorten text consists of 171 sites and is illustrated with 338 pictures. In conclusion it is established that the search for the architectural heritage of the Danubian Monarchy in Bulgaria at the same time a search for the roots of the academic architecture in Bulgaria is.